2017
DOI: 10.5194/os-13-837-2017
|View full text |Cite
|
Sign up to set email alerts
|

A modelling study of eddy-splitting by an island/seamount

Abstract: Abstract.A mesoscale eddy's trajectory and its interaction with topography under the planetary β and nonlinear effects in the South China Sea are examined using the MIT General Circulation Model (MITgcm). Warm eddies propagate to the southwest while cold eddies propagate to the northwest. The propagation speed of both warm and cold eddies is about 2.4 km day −1 in the model. The eddy trajectory and its structure are affected by an island or a seamount, in particular, under certain conditions, the eddy may spli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…However, most eddies may have interactions with topography, strong currents (western boundary current), and other eddies during their lifetime. The motion of an eddy will be modified and even split when approaching an island (Yang et al, 2017). It is also recognized that the western boundary is where eddies disappear (Zhai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most eddies may have interactions with topography, strong currents (western boundary current), and other eddies during their lifetime. The motion of an eddy will be modified and even split when approaching an island (Yang et al, 2017). It is also recognized that the western boundary is where eddies disappear (Zhai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have tried to investigate mesoscale eddies in the NSCS (Wang et al, , 2008Jia et al, 2005). Based on the potential vorticity conservation equation and in situ survey data, Yuan and Wang (1986) pointed out that the bottom topography forcing might be the primary factor for the formation of anticyclonic eddies northeast of Dongsha Islands (DIs). Using survey CTD data in September 1994, Li et al (1998) recorded evidence of anticyclonic eddies in the NSCS and suggested these anticyclonic eddies are probably shed from the KC.…”
Section: Introductionmentioning
confidence: 99%
“…The method was applied to examine the complex trajectories of the 1993-2016 mesoscale ocean eddies in the South China Sea (SCS). It has been well documented that ocean eddies in the SCS split and merge frequently [13,23,24], producing many complex trajectories that are perfect for evaluation of our new method. Eddy splitting events usually lead to current deformation, material dispersion, and subsequent energy decay, which all affect water temperature and salinity, and, consequently, the marine ecosystems [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that ocean eddies in the SCS split and merge frequently [13,23,24], producing many complex trajectories that are perfect for evaluation of our new method. Eddy splitting events usually lead to current deformation, material dispersion, and subsequent energy decay, which all affect water temperature and salinity, and, consequently, the marine ecosystems [23]. By contrast, eddy merging events enhance seawater interaction in different regions and thus affect the trans-scale transmission of energy and entropy in turbulence [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation